Business, Management, and Accounting Research Recommendation - Damara Ardelia Kusuma Wardani; Fritzy Vasya Anandiva; Iman Harymawan; I Wayan Kartana; Mohammad Nasih (Universitas Hayam Wuruk Perbanas, 2025)
This study explores the development of business, management, and accounting research in Indonesia, focusing on publications indexed in SINTA (Science and Technology Index) from 2010 to 2023. Using a Systematic Literature Review (SLR) method, this research examines the patterns of publication growth, challenges, and opportunities faced by Indonesian academics and institutions in business, management, and accounting. The paper proposes the development of a Business Management Accounting Research Ranking (BMARR) platform to systematize and provide easy access to relevant publications. The findings show a significant increase in publications until 2022, but a decline occurred in 2023, indicating potential challenges such as stricter journal selection processes and academic incentives. This study also highlights the dominance of analytical methods in research, while experimental research remains less prevalent. The implications of this research are crucial for academic institutions and researchers to enhance the visibility, impact, and quality of research in the fields of business, management, and accounting in Indonesia. Further efforts are recommended to foster collaboration between academia and institutions and improve the standards of SINTA-indexed journals so that they compete on a global level.